Individual differences in in vitro and in vivo metabolic clearances of antipsychotic risperidone from Japanese subjects genotyped for cytochrome P450 2D6 and 3A5 - Okubo, Maho; Morita, Shoko; Murayama, Norie; Akimoto, Youichi; Goto, Akiko; Yamazaki, Hiroshi (Human psychopharmacology, 2016)
Objective There are conflicting reports regarding the effects of cytochrome P450 (P450, CYP) genotypes on the plasma concentrations of risperidone and its pharmacologically active metabolite, 9‐hydroxyrisperidone (paliperidone), in clinical patients. The aim of this study was to investigate individual differences in the metabolic clearance of risperidone in vitro and in vivo. Methods In vitro liver microsomal risperidone 9‐hydroxylation activities and in vivo plasma concentrations of risperidone and paliperidone were investigated in 15 male and 12 female Japanese subjects (mean age 52 years, range: 24–75 years) genotyped for CYP2D6 and CYP3A5. Results CYP2D6 intermediate and poor metabolizers showed significantly lower liver microsomal risperidone 9‐hydroxylation activities than extensive metabolizers did at 5 μM of risperidone; this difference was not evident at 50 μM of risperidone. The recombinant CYP3A5 Vmax/Km value for risperidone 9‐hydroxylation was 30% that of CYP3A4, and liver microsomes from CYP3A5 expressers had similar risperidone 9‐hydroxylation activities to those of CYP3A5 poor expressers. The plasma concentration/dose ratios for risperidone and paliperidone in 27 Japanese patients were not significantly influenced by the CYP2D6 or CYP3A5 genotypes. Conclusions Individual differences in metabolic clearance of risperidone under the present conditions were not significantly influenced by the genotypes of CYP2D6 or CYP3A5. Copyright © 2016 John Wiley & Sons, Ltd.